Epistemological Synthesis of Hadith Thaharah and WASH Acceleration Framework in Islamic School Sanitation Education - Lubna Lutfia; Norhayati Norhayati; Muhammad Hambal Shafwan (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2026)
Background: The global school sanitation crisis that is far from the 2030 WASH target is driving the need for more effective alternative approaches. In a majority Muslim society such as Indonesia, the concept of taharah in the hadith of the Prophet Muhammad has the potential to become the normative foundation of school sanitation education, but it has never been studied integratively with the international WASH framework. Objective: Analyze the conceptual content of the sahih hadith, map its correspondence with the components of the WASH in Schools Acceleration Framework 2024–2030, and formulate an integrative conceptual framework as the foundation of Islamic value-based sanitation education. Methods: Descriptive-analytical literature research with an integrative review approach . Primary data is sourced from the hadith books of mu'tabar (Al-Lu'lu' wal Marjan, Mukhtashar Saheeh Bukhari-Muslim, Nailul Authar). Data collection was carried out through takhrij al-hadith and systematic literature review based on the PRISMA 2020 protocol. Analysis includes eye analysis, directed content analysis, interpretive synthesis, and source triangulation. Results: Takhrij identified 38 sanitation-related sahih/hasan hadiths classified into six thematic clusters corresponding to six WASH components: safe drinking water, proper sanitation, hand hygiene, menstrual hygiene management, waste management, and changes in hygiene behavior. This study resulted in the Thaharah-WASH Integrative Conceptual Framework (T-WIF). Implications: The T-WIF framework can be operationalized through the revision of the fiqh thaharah curriculum in Islamic schools, advocacy of sanitation infrastructure based on religious arguments, and the development of sustainable behavior change models in the Islamic education environment to support the achievement of SDG 6 in 2030.